Role of In-service Teacher Training as a Tool for the Student’s Performance in Selected Public Secondary Schools in Kisoro District - Ponsiano, Mugarura; Fredrick, Ssempala; Sarah, Nachuha (International Journal of Educational Policy Research and Review, 2022)
In-service training is very important in the life of a learner and general performance of the school. Student achievement is linked to numerous factors, but quality teachers are one of the most important components of student success. If schoolteachers do not have the tools they need to teach students effectively; their students will not get quality education. The major purpose of the study was to assess the role of teacher In-service training as a tool for the student’s performance in selected public schools in Kisoro district. The study applied a mixed methods research design which involved both quantitative and qualitative methods to collect and analyze data. Quantitative data were collected using questionnaire while qualitative data, in-depth interviews. Study sample included the district inspector of schools and District Education Officer and 238 teachers in Kisoro district. It also positively contributes to teacher’s performance. Importantly also, in-service teacher training according to the findings motivates teachers for better results. To teach effectively, teachers need access to ongoing teacher professional development. This professional development enables teachers to improve their own education through seminars, workshops, and classes among others. The study therefore recommends that teachers should frequently be afforded study leaves or time off to do training. During this period, the school can hire part-time teachers so that normal learning is not disrupted. It’s important to appreciate that continual professional development gives teacher’s time to learn and implement new strategies.